Training on Managing Priority Needs to Curb Consumptive Behavior among Students at SMK 1 Pare-pare. - Utami, Dwi; Sri Utami; Magfirah Wahyu Ramadhani; Ambarwati Akib; Nurul Chalisa Majiding (Outline Journal of Community Development, 2025)
Consumptive behavior among students, especially in vocational schools, is a growing concern influenced by low financial literacy and weak self-control in the digital era. This community service program aimed to reduce such behavior through participatory training on needs management. Conducted at SMK Negeri 1 Pare-pare, the program engaged students in interactive sessions, simulations, and discussions to enhance their understanding of financial planning and prioritization. The results showed improved knowledge, increased awareness of spending habits, and a positive shift in attitudes toward money management. The training was well-received by both students and school staff, highlighting the importance of continued financial education. This initiative supports the development of responsible financial behavior among youth.